Can I AI? Kidfluencers And Their Impact on The Marketing Ecosystem: A Qualitative Research - Beata GOTWALD; Bogdan GREGOR; Marlena KOWALCZYK (Communications of International Proceedings, 2024)
This paper explores the emerging role of "kidfluencers" in shaping the marketing ecosystem, focusing on their significant influence on purchasing decisions and their integration into modern marketing strategies. Drawing on theories of consumer socialization and peer influence, the study highlights how children are increasingly seen as active participants in decision-making processes within families and as impactful content creators in digital spaces. A mixed-methods approach, including a comprehensive review of literature and in-depth interviews with eight kidfluencers, reveals the dual role of these young influencers: as agents of consumer trends and as conduits for brand promotion. Key findings indicate that kidfluencers navigate complex dynamics, balancing their roles as content creators and peer influencers while leveraging tools like AI to enhance their creative output. However, the phenomenon raises ethical concerns, including issues related to privacy, parental control, and the psychological impact of social media exposure on children. The study underscores the need for regulatory frameworks to address the exploitation and well-being of child influencers while also exploring the potential of AI as a support tool for content creation in this demographic. These insights contribute to the discourse on marketing ethics, the commodification of childhood, and the transformative impact of kidfluencers on family consumption patterns. Future research is suggested to delve deeper into the financial arrangements of kidfluencers, their long-term influence on consumer behavior, and the evolving role of AI in their content creation strategies.
Keywords: Kidfluencers; Consumer Socialization; Peer Influence; AI in Marketing